Hydrate growth kinetics in marine sediments - Amiya K. Jana (Egyptian Journal of Petroleum)
Clathrate hydrates form and grow when small gas molecules (<0.9 nm) come to contact with water at favorable pressure and temperature conditions. It happens in both the interstitial pore space between distributed marine sediments and inside their nano-meter sized pore spaces. For several thousands of years, the hydrates have occurred abundantly in permafrost and under the sea floor locking an immense amount of energy in the form of natural gas. It is estimated that the total gas reserved in hydrate deposits can meet our primary energy demand for a couple of centuries. To understand their formation and subsequent growth, several formulations have been derived at fundamental level. Various simplified assumptions still make those models really complicated and lead to provide reasonably large errors in prediction. Unfortunately, there is no direct correlation available so far that can precisely predict the hydrate kinetics with most simple way. This work introduces the development of a non-fundamental model routed through the concept of clathrate physics. To investigate the versatility and effectiveness of this growth model, it is used to predict the real-time data comparing with existing physical models.